Model uncertainty and wealth distribution - Edouard Djeutem; Shaofeng Xu (Bank of Canada, 2019)
This paper studies the implications of model uncertainty for wealth distribution in a tractable general equilibrium model with a borrowing constraint and robustness à la Hansen and Sargent (2008). Households confront model uncertainty about the process driving the return of the risky asset, and they choose robust policies. We find that in the presence of a borrowing constraint, model distortion varies non-monotonically with wealth. Robustness generates two forces that amplify wealth inequality. On the one hand, it increases the speed at which the wealth of unlucky households hits the borrowing constraint. On the other hand, it leads richer households to invest a disproportionately larger share of wealth in the higher yielding asset. Our study also shows that model uncertainty results in an aggregate welfare loss unevenly distributed across households.
Keywords: D3; D8; E2; 330; Economic Model; Business fluctuations and cycles; Asset pricing